ANALYSIS OF CORRESPONDENCE BETWEEN SCHOOL CONDITIONS, TEACHING STAFF, AND LEARNING INFRASTRUCTURE ON SCHOOL PERFORMANCE AT SD RICCI 1 WEST JAKARTA CITY - Yosep, Herman; Basir, Choirul (Nindikayla Institute, 2023)
One of the tools to measure a school's progress is school achievement. School achievement is influenced by various factors including the school environment, community environment, and family environment. In this study, researchers limit the problem to the school environment. The school environment is the factor that has the most direct interaction in the world of education, including the school's condition, teaching staff, and learning infrastructure. This study uses correspondence analysis to produce a perception map to find the relationship between the school environment and school achievement in RICCI Elementary School 1 City of West Jakarta. Correspondence analysis reduces variable dimensions and describes the row and column vector profiles of a data matrix from a contingency table. The results obtained are that good achievements are more influenced by the condition of the school and teaching staff and learning infrastructure